2018
DOI: 10.1016/j.cell.2018.02.061
|View full text |Cite|
|
Sign up to set email alerts
|

Tumor-Induced Generation of Splenic Erythroblast-like Ter-Cells Promotes Tumor Progression

Abstract: Identifying tumor-induced leukocyte subsets and their derived circulating factors has been instrumental in understanding cancer as a systemic disease. Nevertheless, how primary tumor-induced non-leukocyte populations in distal organs contribute to systemic spread remains poorly defined. Here, we report one population of tumor-inducible, erythroblast-like cells (Ter-cells) deriving from megakaryocyte-erythroid progenitor cells with a unique Ter-119CD45CD71 phenotype. Ter-cells are enriched in the enlarged splee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 44 publications
8
126
0
Order By: Relevance
“…When we performed differential gene expression analysis between subtype 2 and all other cell subtypes, subtype 2 shows significantly higher SDC1 (also known as CD138) expression levels, increased TFRC (CD71) expression, insignificantly decreased PTPRC (CD45) expression, and significantly decreased PTPRCAP (CD45 associated protein) expression. Since all of the IUSM MM cells in our study had already been FACS sorted for CD138+, it is possible we have identified a population of CD45-/CD71+/CD138+/CD38+ cells in MM with a similar phenotype to the erythroblast-like cells found previously in HCC [34].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…When we performed differential gene expression analysis between subtype 2 and all other cell subtypes, subtype 2 shows significantly higher SDC1 (also known as CD138) expression levels, increased TFRC (CD71) expression, insignificantly decreased PTPRC (CD45) expression, and significantly decreased PTPRCAP (CD45 associated protein) expression. Since all of the IUSM MM cells in our study had already been FACS sorted for CD138+, it is possible we have identified a population of CD45-/CD71+/CD138+/CD38+ cells in MM with a similar phenotype to the erythroblast-like cells found previously in HCC [34].…”
Section: Discussionsupporting
confidence: 57%
“…Upon further examination, we found evidence that subtype 2 may represent a population of erythroblast-like cells in MM. Tumor-inducible erythroblast-like cells have already been reported in hepatocellular carcinoma (HCC) [34]. These CD71+ erythroblast-like cells have been shown in mice to be derived from embryonic stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…2B). Instead, the SCP-like tumor cells expressed genes such as the artemin receptor GFRA3, recently shown to promote hepatocellular carcinoma initiation and growth 25 , and the integrin subunit ITGB8, which is implicated in differentiation and radiosensitization of glioblastoma 26 (Fig. 2B).…”
Section: Sox10+ Cells Expressed Erbb3 and The Ligand Nrg1 Was Expressmentioning
confidence: 99%
“…CD45 is known as a nonerythroid cell marker. To remove the nonerythroid cells from the suspension, CD45-positive cells were excluded from the cell suspension using magnetic separation [18,21]. The resulting purified CD45-negative cells were CD71 high Ter119 high erythroid cells with a purity of 95.2% AE 0.1% (Fig.…”
Section: Flow Cytometry Analysis Of Mouse Spleen-derived Erythroblastmentioning
confidence: 99%